Synergistic Antibacterial and Anti-inflammatory Activities of Ocimum tenuiflorum Ethanolic Extract against Major Bacterial Mastitis Pathogens - Janejira Srichok; Natthika Yingbun; Teerada Kowawisetsut; Sudsaijai Kornmatitsuk; Uthaiwan Suttisansanee; Piya Temviriyanukul; Boonrat Chantong (MDPI AG, 2022)
Mastitis is the most prevalent global illness affecting dairy cows. This bacterial infection damages and inflames the udder tissues. Several plant extracts have demonstrated synergistic antibacterial activities with standard drugs in mastitis treatment. Scant information exists on Ocimum tenuiflorum L. This study evaluated the antibacterial activity of O. tenuiflorum extract and its interaction with antibacterial drugs against common mastitis pathogens including Staphylococcus aureus, coagulase-negative Staphylococci (CNS), Streptococcus agalactiae, and Escherichia coli. Anti-inflammatory activities in LPS-stimulated RAW264.7 macrophage cells were also studied. The O. tenuiflorum extract exhibited antibacterial activities against S. aureus, CNS, and S. agalactiae with minimum inhibitory concentration (MIC) ranging from 3.9 to 31.2 µg/mL and minimum bactericidal concentration (MBC) ranging from 15.6 to 500 µg/mL. Combinations of O. tenuiflorum with penicillin or amoxicillin-clavulanic acid showed synergistic effects against all tested strains but an additive effect with cefazolin and gentamicin. Pretreatment of the extract significantly decreased the expression of inflammatory molecules (IL-6, TNF-α, IL-1β, iNOS, COX-2, and PGE2) generated by LPS in macrophages. Results suggested O. tenuiflorum effectiveness against various Gram-positive mastitis bacteria, with the potential to reduce antibacterial doses and combat inflammation.